2020
DOI: 10.1111/1759-7714.13346
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of CD73 expression for the efficacy of immune checkpoint inhibitors in NSCLC

Abstract: Background CD73 induces the dephosphorylation of adenosine monophosphate converting it to adenosine, enabling malignancies to escape from immune surveillance. Although CD73 overexpression has been reported to be a poor prognostic factor in several malignancies including non‐small cell lung cancer (NSCLC), its predictive relevance in NSCLC patients receiving immune checkpoint inhibitors is unknown. The present research was conducted to investigate the prognostic significance of CD73 expression in NSCLC patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…By contrast, Ishii et al retrospectively showed that high CD73 expression correlated with favorable clinical efficacy of immunotherapy in patients with EGFR-mutated NSCLC who have developed resistance to EGFR-TKIs, although this study had some limitations such as the limited number of patients analyzed (63).…”
Section: Immunometabolism Mediated By Cd39/cd73 -Adenosine Axis In Egmentioning
confidence: 85%
See 1 more Smart Citation
“…By contrast, Ishii et al retrospectively showed that high CD73 expression correlated with favorable clinical efficacy of immunotherapy in patients with EGFR-mutated NSCLC who have developed resistance to EGFR-TKIs, although this study had some limitations such as the limited number of patients analyzed (63).…”
Section: Immunometabolism Mediated By Cd39/cd73 -Adenosine Axis In Egmentioning
confidence: 85%
“…CD73 is endogenously expressed on endothelial cells, epithelial cells, and some immune subsets, and its expression has also been observed in several cancer types, including melanoma, colon, breast, ovarian, and lung cancer (19). Notably, the main drivers of CD73 expression within TME include hypoxia, TGF-β, type I IFN, IL-1, and prostaglandin (63).…”
Section: Immunometabolism Mediated By Cd39/cd73 -Adenosine Axis In Egmentioning
confidence: 99%
“…We here for the first time show that PEA can be used to decipher immune and tumor signaling in minute FNA material also from NSCLC lesions. Some of these immune signaling components are reported to be of relevance to response to ICIs [ 13 , 23 , 25 , 27 , 28 , 36 ]. Thus, our study points at a possible path to overcome certain of the challenges for interventional oncology as previously outlined by Schoenberg et al .…”
Section: Discussionmentioning
confidence: 99%
“…Signaling in tumor cells per se or its microenvironment is an important driver for both intrinsic and acquired therapy resistance to both targeted therapy as well as to ICIs [ 13 , 23 , 25 , 27 , 28 , 36 ]. Here, we report analysis of pairwise consecutive FNA samples from six patients and compared expression of > 160 different proteins.…”
Section: Discussionmentioning
confidence: 99%
“…First, for enzymatic function, CD73 is a rate-limiting enzyme in the production of extracellular adenosine. High concentration of CD73-generated adenosine in microenvironment is an anti-inflammatory agent, which prevents excess inflammatory reactions and has been shown to be involved in tumor immunity escapes ( Chen et al, 2020 ; Ishii et al, 2020 ). Thus, CD73-adenosine axis have been considered as a further immune checkpoint to exploit target treatment.…”
Section: Discussionmentioning
confidence: 99%